Criticism of Philosophical Approaches to Sociolinguistics - Siregar, Iskandarsyah (Budapest International Research and Critics University, 2022)
One of the branches of linguistics that are most actively used and the most widely questioned is Sociolinguistics. Sociolinguistics is a linguistics science that seeks to express the values of life that are revealed in language. Sociolinguistics is stuck in the study of language, which is purely empirical. This assessment can be observed when sociolinguistics only comes to the study of language, which reveals the linguistic system. It is essential to point out the other side of sociolinguistics that has not been explored, namely the aspect of language meaning. In this case, philosophical approach tries to challenge the existence of sociology concerning the role and function of sociolinguistics itself. Through literature study, Hermeneutics and heuristics are consistently and consistently used as the basis for the research method in this case. The research that forms the basis for writing this scientific article begins with a study with literature observations. It can be concluded that sociolinguistics must start to view language as a form of culture that becomes a social system and acts as a tool for human development.